(untitled) (Research, Society and Development, 2022)
Given the composition of the individual’s social identity and his perception as an active agent of history. Based on the assumption that the construction of a global history takes place from an infinity of plural histories built over time, which deserve respect and visibility in an egalitarian way, it is also sought to enable the construction of the historical consciousness of the subjects, providing an active relationship with the moment and space where the students live. The methodology adopted is based on the proposal of a bibliographic study, allied to a field research, in loco, seeking to unite theories and concepts to the existing reality in the present day. marginalized individuals from the historical process come to know and value their experiences, it is therefore necessary to rethink the local context in the face of teaching and the importance of cultural reconstruction of the municipality of Fagundes, considering that the local analysis, in the context of basic education , allows us a new possibility of dialogue, permeating the reflection about our identity and encouraging dialogue between different identities, encouraging the posture of agents of social transformation.